Jet Lag, Stress, and Behavioural Changes of Daily Living on Umrah Pilgrims from Indonesia - Eko Mulyadi (Journal of Global Pharma Technology, 2016)
Introduction:Umrah is an Islamic pilgrimage to Mecca that can be undertaken at any time of the year the Umrah pilgrims who depart from Indonesia to Saudi Arabia has air travel for 10 hours, this study aims to observe the phenomena umrah pilgrim from Indonesia conducted in Indonesia and Saudi Arabia with a long time of 18 days. Method:This study involved 14 participants who perform umrah pilgrims, by using interview technique and direct observation. Research design used a qualitative study with a phenomenological approach. Results:The result of the study showed that pilgrims experience jet lag, also stressed. Disturbance sleep. and behavioral change of daily living. Although umrah (pilgrims) is a spiritual activity, but the implementation made the pilgrims stressed, long flight up to 10 hours with boarding matter, visa examination, made the pilgrims stressed. Conclusion:Umrah pilgrims who experience stress will affect their physical condition. Where physical conditions will affect other biological conditions. including its ability to worship.Keywords: Jet Lag Syndrome, Umrah pilgrims, Stress.